Contemporaneity of the Portuguese language in Japan - Ichinose, Atsushi (2005)
The objective of this article is to disseminate more and better the current situation of the Portuguese language in Japan and it reveals the reality that this language brought to the Japanese people in order to develop the teaching of Portuguese in that country and to determine, with greater precision, the position of this language in today's world.